ANALYSIS OF THE LEGISLATIVE FUNCTION OF BANYUASIN REGENCY LEGISLATIVE COUNCIL MEMBERS DURING THE RECESS PERIOD - Kariem, Muhammad Quranul; Ishmatuddin, Noor (Journal of Governance and Public Policy, 2020)
This study aims to determine the effectiveness of the recess carried out by the Banyuasin District Parliament with a theoretical approach from Harel Arnon on direct legislation. The qualitative approach method used interviews with informants, then the data found were broken down and analyzed with theory, and conclusions drawn. The results found that the recess period carried out by the Banyuasin District Parliament in the process was effective because it could encourage increased community participation in development issues. The factor that made the exercise of the recess period effective was because the majority geographical area was quite difficult to reach by board members.